2002
DOI: 10.1038/sj.eye.6700046
|View full text |Cite
|
Sign up to set email alerts
|

A new method of biofeedback in the management of low vision

Abstract: Twenty-eight patients with low vision were enrolled into the study. A preliminary study was carried out on 18 eyes of 13 patients with low vision who underwent visual rehabilitation with a new instrument for biofeedback (BF) applied to vision; improved biofeedback integrated system (Ibis). Successively, eight patients (16 eyes) with bilateral low vision were subjected to biofeedback in one eye. The experimental and control eye were evaluated separately. Then a placebo training was developed on seven patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 17 publications
2
24
1
1
Order By: Relevance
“…In a preliminary study as reported by Contestabile et al (2002) on 18 eyes of 13 patients with low-vision who underwent visual rehabilitation with a new instrument for biofeedback showed an increase in visual performances (Visual acuity, colour vision, automated perimetry, contrast sensitivity and flash VEP), related to a control group in which no treatment was performed. As found by Giorgi et al (2005) in one hundred and ten patients (179 eyes) with reduced visual acuity caused by different ocular disorders, who underwent visual rehabilitation with an instrument for biofeedback: improved biofeedback integrated system (Ibis), improved visual acuity in 130/179 eyes (72.62%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a preliminary study as reported by Contestabile et al (2002) on 18 eyes of 13 patients with low-vision who underwent visual rehabilitation with a new instrument for biofeedback showed an increase in visual performances (Visual acuity, colour vision, automated perimetry, contrast sensitivity and flash VEP), related to a control group in which no treatment was performed. As found by Giorgi et al (2005) in one hundred and ten patients (179 eyes) with reduced visual acuity caused by different ocular disorders, who underwent visual rehabilitation with an instrument for biofeedback: improved biofeedback integrated system (Ibis), improved visual acuity in 130/179 eyes (72.62%).…”
Section: Discussionmentioning
confidence: 94%
“…Giorgi et al (2005), Contestabile et al (2002), Mezawa et al (1990) have proposed different visual rehabilitation techniques using biofeedback strategies starting from basic systems like accomotrack or IBIS devices, merging to more complex instruments as the visual pathfinder. Recently introduced techniques, such as microperimetry by SLO, as reported Fujii et al (2002) and Nilsson et al (2003), lead us to a better knowledge of the cognitive processes of rehabilitation and more serve as a diagnostic tool for the follow-up of AMD patients.…”
mentioning
confidence: 99%
“…In ophthalmology, various techniques of biofeedback, such as plain light stimulus,1 acoustic biofeedback,2 and structured light stimulus plus acoustic biofeedback3 have been applied to congenital nistagmus,4 amblyopia,5,6 macular disease,7 and emianopia8,9 and have proved to be efficacious in the improvement of visual function in these disorders. In 1993, Rauscher et al10 found that listening to Mozart music could improve the IQ (intelligence quotient) score of students, as opposed to listening to relaxation instructions or silence.…”
Section: Introductionmentioning
confidence: 99%
“…Ibis is composed of an optical and an electronic unit as reported in our previous paper (Figs. 1 and 2) (Contestabile et al, 2002).…”
mentioning
confidence: 99%